The role of the dielectric environment in surface‐enhanced Raman scattering on the detection of a 4‐nitrothiophenol monolayer. (19th June 2013) - Funke, Sebastian; Wackerbarth, Hainer
<x xml:space="preserve">Abstract</x> Nanotechnology enables the generation and characterization of novel surface‐enhanced Raman scattering (SERS) substrates. In this study, we focus on the impact of the carrier material of the SERS active layer and hence the dielectric environment to the enhancement. Therefore, a self‐assembled monolayer of 4‐nitrothiophenol is immobilized on silver and gold particles substrates on a quartz carrier. The detection of the monolayer occurs through the quartz carrier and through air. For the former, an increase of the intensity of the SERS bands in the spectrum is observed compared to the latter. The magnitude of the increase is larger for gold than for silver. Calculations according to the theoretical model of the electromagnetic enhancement agree with our experimental data. The presented detection mode will stimulate the fabrication of novel SERS sensors. Copyright © 2013 John Wiley & Sons, Ltd.